Predicting Depression with Psychopathology and Temperament Traits: The Northern Finland 1966 Birth Cohort. (16th August 2012) - Miettunen, Jouko; Isohanni, Matti; Paunio, Tiina; Freimer, Nelson; Taanila, Anja; Ekelund, Jesper; Järvelin, Marjo-Riitta; Joukamaa, Matti; Lichtermann, Dirk; Koivumaa-Honkanen, Heli; Veijola, Juha
Abstract : We studied the concurrent, predictive, and discriminate validity of psychopathology scales (e.g., schizotypal and depressive) and temperament traits for hospitalisations due to major depression. Temperament, perceptual aberration, physical and social anhedonia, Depression Subscale of Symptom Checklist (SCL-D), Hypomanic Personality Scale, Schizoidia Scale, and Bipolar II Scale were completed as part of the 31-year follow-up survey of the prospective Northern Finland 1966 Birth Cohort (n = 4941; 2214 males). Several of the scales were related to depression. Concurrent depression was especially related to higher perceptual aberration (effect size when compared to controls, d = 1.29 ), subsequent depression to high scores in SCL-D (d = 0.48 ). Physical anhedonia was lower in subjects with subsequent depression than those with other psychiatric disorders (d = −0.33, nonsignificant). Participants with concurrent (d = 0.70 ) and subsequent (d = 0.54 ) depression had high harm avoidance compared to controls, while differences compared to other psychiatric patients were small. Subjects with depression differed from healthy controls in most of the scales. Many of the scales were useful predictors for future hospital treatments, but were not diagnosis-specific. High harm avoidance is a potential indicator for subsequent depression.